2005
DOI: 10.1377/hlthaff.24.2.459
|View full text |Cite
|
Sign up to set email alerts
|

What If We Were Equal? A Comparison Of The Black-White Mortality Gap In 1960 And 2000

Abstract: ABSTRACT:The United States has made progress in decreasing the black-white gap in civil rights, housing, education, and income since 1960, but health inequalities persist. We examined trends in black-white standardized mortality ratios (SMRs) for each age-sex group from 1960 to 2000. The black-white gap measured by SMR changed very little between 1960 and 2000 and actually worsened for infants and for African American men age thirty-five and older. In contrast, SMR improved in African American women. Using 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
161
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(166 citation statements)
references
References 7 publications
4
161
0
1
Order By: Relevance
“…We therefore selected beneficiaries for whom we could demonstrate continuing use of the direct care system during the duration of the study. Study beneficiaries were identified using the following inclusion criteria: (1) Age Ͼ18 yr-old; (2) Outcomes Figure 1 shows the outcomes assessed during the study, which for purposes of uniformity are referred to collectively as targets. To avoid bias due to differences in follow-up among beneficiaries, in which beneficiaries with longer potential follow-up might have a higher frequency of outcomes, outcomes were assessed over a 12-mo period from the date of the first test used to determine the entry eGFR, but no later than the end of the study date, because it was assumed the stage of CKD during this first test would determine further medical treatment.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore selected beneficiaries for whom we could demonstrate continuing use of the direct care system during the duration of the study. Study beneficiaries were identified using the following inclusion criteria: (1) Age Ͼ18 yr-old; (2) Outcomes Figure 1 shows the outcomes assessed during the study, which for purposes of uniformity are referred to collectively as targets. To avoid bias due to differences in follow-up among beneficiaries, in which beneficiaries with longer potential follow-up might have a higher frequency of outcomes, outcomes were assessed over a 12-mo period from the date of the first test used to determine the entry eGFR, but no later than the end of the study date, because it was assumed the stage of CKD during this first test would determine further medical treatment.…”
Section: Patient Populationmentioning
confidence: 99%
“…Blacks have been shown to experience higher mortality, less access to care, higher risk of renal disease progression, fewer referrals for renal transplantation, and shorter renal allograft survival than Whites (1)(2)(3)(4)(5). Some programs aimed at enhancing access to care have shown improvements in this health gap (6,7).…”
mentioning
confidence: 99%
“…Since the 1960s, the mortality rate for blacks has been 50 percent higher than that for whites, and the infant mortality rate for blacks has been twice as high as that for whites. 2,3 Health disparities exist even in health care systems that offer patients similar access to care, such as the Department of Veterans Affairs, 4 which suggests that disparities originate outside the formal health care setting.…”
mentioning
confidence: 99%
“…10 One study found that closing the black-white mortality gap would eliminate a startling "83,000 excess deaths per year among African Americans." 11 …”
Section: Disparities In Health Statusmentioning
confidence: 99%